RE: Percutaneous nephrolithotomy for isolated calyceal stones: How important is the stone location? - Kamarulzaman, Mohd Nazli (Turkish Association of Urology, 2016)
I read with great interest the article “Percutaneous nephrolithotomy for isolated calyceal stones: How important is the stone location?” by Ozgor et al.[1] This article highlights an interesting outcome of isolated calyceal stones which were managed by percutaneous nephrolithotomy (PCNL). The isolated upper pole calyceal stone has been shown to have statistically significant difference in term of thoracic complications, longer nephrostomy duration, and hospital stay in comparison to middle calyceal stone. Besides that, post-operative bleeding also appeared to be higher and stone clearance rate was lower in upper pole puncture but there was no statistically significant difference between the groups. All those parameters suggest that the direct puncture for treating isolated upper pole calyceal stone has higher risks with lower effectiveness. In my opinion a definite conclusion cannot be drawn from this study as it was a retrospective review which had some limitations. In this study various modifications of conventional PCNL as a special measure was not clearly elaborated. The use of balloon dilatation and single stage dilatation with Amplatz dilator was found to have less bleeding in comparison to serial Amplatz dilatation.[2] Whereas properly selected site and timing of the puncture was found to reduce the thoracic complications. Ko et al.[3] found that careful placing the puncture site at lateral half of the ribs will avoid pleural and supracostal puncture. Whereas, puncturing kidney during fully expiration will push the lung base two interspaces higher. Both tricks will avoid from puncturing pleura, thus reduce thoracic complications.